Pengaruh Firm Size, Return On Equity, dan Current Ratio Terhadap Tax Avoidance pada Perusahaan LQ 45 yang Terdaftar di Bursa Efek Indonesia - Rosa Cristiana Septya Nyman; Irawan Perdanaputra Kaidun; Ita Salsalina Lingga (Jurnal Akuntansi, 2022)
Tax Avoidance represents a strategy that taxpayers have planned to take advantage of tax loopholes to reduce their tax obligations. The Directorate General of Taxes suspects that  PT Adaro Energy Tbk is having Tax Avoidance issues due to the introduction of transfer pricing by a Singapore subsidiary. PT Adaro has implemented transfer pricing. If the problem is true,  it can be classified as Tax Avoidance. This study aims to identify the impact of company size, return on equity, and current ratios on Tax Avoidance. This study is a  category of causal explanatory studies in which samples are selected using a purposeful sampling method and hypotheses are tested using multiple regression testing. In this survey, the population and sample are LQ 45 companies listed on the Indonesia Stock Exchange between 2016 and 2019, with a population of 45 companies and a sample of 34 companies. The Tax Avoidance measurement in this study uses the effective tax rate (ETR). The results of this study explain that corporate size affects Tax Avoidance, while return on equity and current ratios do not affect Tax Avoidance. Keywords: Firm Size, Return on Equity, Current Ratio, and Tax Avoidance